2021
DOI: 10.3390/ijms22062840
|View full text |Cite
|
Sign up to set email alerts
|

Palindromes in DNA—A Risk for Genome Stability and Implications in Cancer

Abstract: A palindrome in DNA consists of two closely spaced or adjacent inverted repeats. Certain palindromes have important biological functions as parts of various cis-acting elements and protein binding sites. However, many palindromes are known as fragile sites in the genome, sites prone to chromosome breakage which can lead to various genetic rearrangements or even cell death. The ability of certain palindromes to initiate genetic recombination lies in their ability to form secondary structures in DNA which can ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 127 publications
(161 reference statements)
2
26
0
Order By: Relevance
“…Irrespective of whether we consider microdeletions or gross deletions, the mechanisms underlying pathogenic deletions appear to be strongly influenced by the local DNA sequence environment (Kondrashov & Rogozin, 2004;Krawczak & Cooper, 1991). The role of non-B DNA structures in the formation of cancer-associated deletions, as well as deletions in the germline and in mitochondrial sequences, has been appreciated for some time (Bacolla et al, 2016(Bacolla et al, , 2019Damas et al, 2014;Dong et al, 2014;Fontana & Gahlon, 2020;Pabis, 2021;Svetec Miklenić & Svetec, 2021;Zhao et al, 2010). Such non-B DNA structures often have key regulatory functions in DNA replication and transcription but may also cause genomic instability (Lemmens et al, 2015;Zhao et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of whether we consider microdeletions or gross deletions, the mechanisms underlying pathogenic deletions appear to be strongly influenced by the local DNA sequence environment (Kondrashov & Rogozin, 2004;Krawczak & Cooper, 1991). The role of non-B DNA structures in the formation of cancer-associated deletions, as well as deletions in the germline and in mitochondrial sequences, has been appreciated for some time (Bacolla et al, 2016(Bacolla et al, , 2019Damas et al, 2014;Dong et al, 2014;Fontana & Gahlon, 2020;Pabis, 2021;Svetec Miklenić & Svetec, 2021;Zhao et al, 2010). Such non-B DNA structures often have key regulatory functions in DNA replication and transcription but may also cause genomic instability (Lemmens et al, 2015;Zhao et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when using Cas9-induced DSBs at individual sites to study regulation of DSB repair pathway choices, we should avoid generalization unless it is taken into consideration how Cas9-sgRNA interacts with its target and is released from it after DNA cleavage. In addition, repair of the three-ended DSBs provides an opportunity for the DNA ends of two sister chromatids to rejoin, not only creating a palindromic chromosome with two centromeres or no centromere [42,43], but also leaving the third end for potential translocation. Both dicentric and acentric palindromic chromosomes are unstable and serves as a potential source for chromothripsis and complex chromosomal rearrangements including large deletions and insertions at the target site [40][41][42][43]54].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, repair of the three-ended DSBs provides an opportunity for the DNA ends of two sister chromatids to rejoin, not only creating a palindromic chromosome with two centromeres or no centromere [42,43], but also leaving the third end for potential translocation. Both dicentric and acentric palindromic chromosomes are unstable and serves as a potential source for chromothripsis and complex chromosomal rearrangements including large deletions and insertions at the target site [40][41][42][43]54]. Therefore, this study identi es a potential mechanism underlying on-target chromosomal rearrangements previously detected in CRISPR/Cas9 genome editing [55][56][57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…Our observations suggest that the M. oryzae genome is divided into genes needed for interaction with the environment similarly surrounded by house-keeping genes as described for the non-conserved regions in Fusarium graminearu m where these types of genes are overrepresented (Zhao et al, 2014). One of the most potential DNA-binding sites for the MoISW2 is a palindromic motif giving instability to the genome at this site (Ganapathiraju et al, 2020; Svetec Miklenić and Svetec, 2021) and characteristic of motifs for retrotransposons situated close to stress-related genes and avirulence genes (plant pathogen effectors with a difference in resistance against by cultivars, thus the cause of avirulence against these cultivars)(Yoshida et al, 2016). The authors also found that a gene linkage to transposons is connected with elevated mutation rates.…”
Section: Discussionmentioning
confidence: 99%